KUALITAS PRODUK PANDAN SAGO WITH ICE CREAM DI NONGSA POINT MARINA & RESORT BATAM - Ulina, Tio Lina Roma; Sidiq, Rd. Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Nongsa Point Marina (NPM) is a four star resort in the Riau Island and is part of the Nongsa Resort group. Nongsa Resort itself consists of 3 resorts, namely Turi Beach, Nongsa Point Marina, and Taman Nongsa Indah Village (TNIV). There are around 20 choices of appetizer menus consisting of indonesia food, western food, snacks, sweets offered by the cold kitchen section of Nongsa Point Marina & Resort Batam. One of them is Pandan Sago With Ice Cream. Pandan Sago With Ice Cream has a very creamy texture, using the raw material of sagp pearls combined with the savory original kara coconut milk and the sweetness of palm sugar, as well as the aroma of Pandan which really sttracts attention and appetite, then a very special combination when Vanilla Ice Cream is in between the circles Pandan Sago. Feedback is one way to get guest’s opinions about the products offered at hotels or resort. This research was conducted to find out how guest respon regarding the influence of the quality of Pandan Sago With Ice Cream products on guest satisfaction at Nongsa Point Marina & Resort Batam. This research uses a quantitative descriptive method with a sample size of 100 respondents based on the last year’s population. The data collection tchniques used by the author are observation, questionnaires, documentation and using a likert scala as a measuring tool. Based on research result, the influence of Pandan Sago With Ice Cream product quality on guest satisfaction at Nongsa Point Marina & Resort Batam in the category is good. Keywords : Influence, Product Quality, Guest Satisfaction